2008
DOI: 10.1007/s00442-008-0987-0
|View full text |Cite
|
Sign up to set email alerts
|

Animal movement in dynamic landscapes: interaction between behavioural strategies and resource distributions

Abstract: Most ecological and evolutionary processes are thought to critically depend on dispersal and individual movement but there is little empirical information on the movement strategies used by animals to find resources. In particular, it is unclear whether behavioural variation exists at all scales, or whether behavioural decisions are primarily made at small spatial scales and thus broad-scale patterns of movement simply reflect underlying resource distributions. We evaluated animal movement responses to variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
98
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(104 citation statements)
references
References 65 publications
3
98
0
Order By: Relevance
“…Increased densities of noncommercial unexploited benthic fishes inside marine reserves could also act as a source of potential prey for the mobile species, and therefore either attract mobile fishes or help retain them within reserves Jones 2001, Beukers-Stewart andJones 2004). Moreover, factors other than resources could induce complex behavioral patterns (Roshier et al 2008) and fishing pressure outside could attract species inside reserves (Eggleston and Parsons 2008). It has been shown that fish species can modify their daily home range and seasonal displacement based on the local social dynamics and their social status (Afonso et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Increased densities of noncommercial unexploited benthic fishes inside marine reserves could also act as a source of potential prey for the mobile species, and therefore either attract mobile fishes or help retain them within reserves Jones 2001, Beukers-Stewart andJones 2004). Moreover, factors other than resources could induce complex behavioral patterns (Roshier et al 2008) and fishing pressure outside could attract species inside reserves (Eggleston and Parsons 2008). It has been shown that fish species can modify their daily home range and seasonal displacement based on the local social dynamics and their social status (Afonso et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Optimal movement decisions of animals are to a certain extent influenced by individual ability to learn and navigate through a landscape of heterogeneous resource patches (Bélisle 2005;Roshier et al 2008), which in DGR was shown by the varied movement patterns of different lions. As this study demonstrates, behavioural responses of lions to forced dispersal of reintroduction, their subsequent ways in exploring and adapting to a new habitat and optimal movement decisions can differ greatly between individuals, depending on intraspecific interactions, habitat preferences, human disturbances and individual experiences that vary in spatial and temporal scales.…”
Section: Discussionmentioning
confidence: 99%
“…Animals may use different areas within home ranges for different behaviors due to the spatial distribution of different resources (Marzluff et al 2001, Indermaur et al 2009). Exploring the relative importance of factors governing habitat selection across spatial scales can therefore shed light on the decision rules underlying animal movements (Roshier et al 2008).…”
Section: Introductionmentioning
confidence: 99%